The Policy of Moral Education on KH Imam Zarkasyi’s Thought at Gontor Modern Islamic Boarding School - Karnaen, Abdul; Hakim As-Shidqi; Akrim Mariyat (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2014)
KH. Imam Zarkasyi is one of the founding fathers of Gontor Modern Islamic Boarding School and also a famous national figure. The writer proposes to study moral education especially in the perspectives of KH. Imam Zarkasyi. The writer describes KH. Imam Zarkasyi’s definition of moral education, then the measurement of moral and method of teaching moral. The study is found that moral is action science, or knowledge about things that shows the good and bad elements in living in society, and moral education is action education or delivering the knowledge on the measurement of moral, that shows the bad and good things in living in society, and the measurement is the absolute one. Moral education can be categorized into two; physical and spiritual moral education. Here, the writer concludes that in inculcating moral, there is no difference between physical and spiritual, but the integrated system as one education method.